2002
DOI: 10.1128/aem.68.1.114-123.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Lactobacillus spp. and Other Lactic Acid Bacteria in the Human Intestine as Determined by Specific Amplification of 16S Ribosomal DNA

Abstract: A Lactobacillus group-specific PCR primer, S-G-Lab-0677-a-A-17, was developed to selectively amplify 16S ribosomal DNA (rDNA) from lactobacilli and related lactic acid bacteria, including members of the genera Leuconostoc, Pediococcus, and Weissella. Amplicons generated by PCR from a variety of gastrointestinal (GI) tract samples, including those originating from feces and cecum, resulted predominantly in Lactobacillus-like sequences, of which ca. 28% were most similar to the 16S rDNA of Lactobacillus ruminis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
370
2
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(401 citation statements)
references
References 53 publications
(42 reference statements)
12
370
2
8
Order By: Relevance
“…Many of the other bacteria enriched on the mucosa, such as Campylobacter spp., Weissella spp, and Sutterella spp., are known mucosal colonizers or pathogens and are likely mucosal specialists (On, 1996). These genera may be broadly specific to mucosal surfaces across mammals, having been identified on the mucosal surfaces of multiple host species (On, 1996;Heilig et al, 2002;Green et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Many of the other bacteria enriched on the mucosa, such as Campylobacter spp., Weissella spp, and Sutterella spp., are known mucosal colonizers or pathogens and are likely mucosal specialists (On, 1996). These genera may be broadly specific to mucosal surfaces across mammals, having been identified on the mucosal surfaces of multiple host species (On, 1996;Heilig et al, 2002;Green et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Those sequences that were not already curated in this database were extracted from the EMBL database using the public Sequence Retrieval System (SRS) server at EBI (Zdobnov et al, 2002). The 16S rRNA sequence of the Bacillus subtilis type strain was added as outgroup, since previous analyses have suggested that enterococci and streptococci are too close to the lactobacilli to use as outgroups for 16S phylogeny (Heilig et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…It has been extensively studied for its probiotic properties in human trials and animal models (Dunne et al, 1999(Dunne et al, , 2001McCarthy et al, 2003;Sheil et al, 2004). Members of this species are commonly isolated from the oral and GI tracts of humans and other animals (Ahrne et al, 1998;Heilig et al, 2002;Molin et al, 1993;Rogosa et al, 1953). The 2?13 Mb genome of L. salivarius UCC118 comprised a 1?83 Mb chromosome, a 242 kb megaplasmid and two smaller plasmids of 20 kb and 44 kb.…”
Section: Introductionmentioning
confidence: 99%
“…'Infant K' did not yield Lactobacillus at any time point by either culturing or DGGE. Heilig et al (2002) studied the development of the Lactobacillus-like community in infants by PCR on fecal DNA from a baby from delivery (day 1) to 5 months later (day 147) at regular intervals. No PCR products were obtained up to day 55, indicating that the template was absent or that the amount of template was too low to be detected.…”
Section: Discussionmentioning
confidence: 99%